Protective Effect of Gallic Acid on Testicular Tissue, Sperm Parameters, and DNA Fragmentation against Toxicity Induced by Cyclophosphamide in Adult NMRI Mice - Mehraban, zahra; Ghaffari Novin, Marefat; Golmohammadi, Mohammad Ghasem; Sagha, Mohsen; Ziai, Seyed Ali; Abdollahifar, Mohammad Amin; Nazarian, Hamid (Urology Journal, 2020)
Purpose: This study aimed to investigate the protective effect of Gallic acid (GA) on the Cyclophosphamide (CP) toxicity induced in the reproductive system. Materials and Methods: After a pilot study for dose responses of Gallic acid ,Forty adult male NMRI mice were divided into 5 groups (n=8): control, sham (NaCl Serum: 0.2mL per day), CP (15 mg kg-1 per week; IP), GA (12.5 mg kg-1 per day ; IP) and GA (12.5 mg kg-1 per day ; IP) +CP(15 mg kg-1 per week; IP). After treatment, the left testis was detached and used for Histological examination and right testis used for Malondialdehyde (MDA) measures. Left caudal epididymis was placed in the Ham’s F10 medium and released spermatozoa were used in order to analyze sperm parameters. Sperm DNA fragmentation was assessed by Sperm Chromatin Dispersion (SCD) method. Results: In the CP group, there was a significant increase in the sperm DNA fragmentation (% 57.89 ± 23.91) compared with control group (% 24.52 ± 10.27). That was significantly improved by GA (12.5 mg kg-1 per day ; IP) in GA+CP group (% 28.4 ± 8.85) compared to CP group (p< .001). A significant increase was reported about MDA levels in CP group (6.26 ± 2.59) in compared with the control group (4.30 ± 2.05), But GA (3.24 ± 1.33) decreased it in GA+ CP group (p< .01). The histopathological investigation revealed marked testicular atrophy in CP group, whereas GA diminished these deviations (P< .05). Conclusion: Gallic acid can modify the reproductive toxicity of cyclophosphamide in NMRI mice and increase the antioxidant capacity of testis tissue.